ICare® Home vs Goldmann applanation tonometry: Agreement of methods and comparison of inter-observer variation at a tertiary eye centre. Issue 1 (January 2023) - Quérat, Laurence; Chen, Enping
Purpose: To investigate whether the inter-observer variation is similar between the Goldmann applanation tonometer used by healthcare staff and the iCare® Home tonometer used by glaucoma patients, volunteers and healthcare staff.Methods: Sixty-one participants were recruited to the study, including 24 glaucoma patients. Seven participants were excluded. For each participant, intraocular pressure (IOP) was measured on the same occasion by two different healthcare staff using GAT as well as by a healthcare staff and the participant using the iCare® Home tonometer.Results: Seventy-two per cent of iCare® measurements were within 3 mmHg of the GAT measurements. There was a statistically significant difference between the trainers' measurements made with iCare® Home and those made with GAT ( p  < 0.001), as well as between the GAT measurements made by trainers and those made by extra personnel ( p  = 0.017). The strongest correlation was between iCare® Home participants' and trainers' measurements (0.934). The correlation between different users with GAT was lower (0.769). The inter-user agreement was excellent for iCare® Home users (95% CI 0.93, ranging from 0.880 to 0.959) and moderate for GAT users (95% CI 0.741, ranging from 0.558 to 0.849).Conclusion: Our study found that tonometry with iCare® Home has similar or less inter-user variation compared with GAT.